The case of the stolen baseball card - Preller, James; Smith, Jamie; Alley, R. W. (Robert W.); Copyright Paperback Collection (Library of Congress) (New York : Scholastic Inc., 1999)
Jigsaw is out to discover why tough Bigs is acting so oddly, reading babysitter club books and sneaking around.
"A Little Apple paperback."
G2
Keywords: Detective and mystery stories; Children's stories; Mystery fiction